2001
DOI: 10.1002/ijc.1030
|View full text |Cite
|
Sign up to set email alerts
|

Induction of interleukin‐1β and interleukin‐6 mRNA by low doses of ionizing radiation in macrophages

Abstract: SUMMARYWe have previously reported the antimetastatic effects and augmentation of immune responses, which would be a mechanism of the antimetastatic effects, of 0.1 to 0.2 Gy total body irradiation. To elucidate the cellular mechanisms of the augmentation of immune response, we investigated the effects of low-dose irradiation on gene expression of interleukin-1␤ (IL-1␤) and IL-6 using mouse peritoneal macrophages in vitro. Absolute mRNA quantification was carried out using competitive polymerase chain reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 33 publications
2
26
0
Order By: Relevance
“…Interestingly, expression of connexin43 has been shown to be regulated by IL-1b (Tonon and D'Andrea, 2002), basic fibroblast growth factor (bFGF) (Doble and Kardami, 1995), TNF-a (Fernandez-Cobo et al, 1999) and several other molecules (De Maio et al, 2002). Regulation of IL-1b (Hosoi et al, 2001), bFGF (Haimovitz-Friedman et al, 1991), TNF-a (Weill et al, 1996) and IL-8 (Narayanan et al, 1999) was previously shown to be sensitive to ionizing radiation. Other radiation released cytokines and growth factors may also be involved (Narayanan et al, 1999;Barcellos-Hoff and Brooks, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, expression of connexin43 has been shown to be regulated by IL-1b (Tonon and D'Andrea, 2002), basic fibroblast growth factor (bFGF) (Doble and Kardami, 1995), TNF-a (Fernandez-Cobo et al, 1999) and several other molecules (De Maio et al, 2002). Regulation of IL-1b (Hosoi et al, 2001), bFGF (Haimovitz-Friedman et al, 1991), TNF-a (Weill et al, 1996) and IL-8 (Narayanan et al, 1999) was previously shown to be sensitive to ionizing radiation. Other radiation released cytokines and growth factors may also be involved (Narayanan et al, 1999;Barcellos-Hoff and Brooks, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Proteasome inhibition would be expected to prevent NF-kB activation, but numerous studies have shown radiation to activate it (Li and Karin, 1998;Raju et al, 1998). Activation of NF-kB is considered to mediate radiation-induced proinflammatory responses, and irradiation of cells and tissues increases expression of proinflammatory chemokines (Johnston et al, 2002) and cytokines such as TNF-a (Hallahan et al, 1989;Chiang et al, 1993), IL-1a and -b (Hong et al, 1994;Hosoi et al, 2001), IL-5 (Lu-Hesselmann et al, 1997), IL-6 (Abeyama et al, 1995;Beetz et al, 1997), GM-CSF (Zhang et al, 1994), IFN-a (Woloschak et al, 1990), bFGF (Haimovitz-Friedman et al, 1991), and VEGF (Gorski et al, 1999;Park et al, 2001), as well as proinflammatory cell adhesion molecules (ICAM-1 (Behrends et al, 1994;Hong et al, 1994;Gaugler et al, 1997), E-selectin (Hallahan et al, 1995), and VCAM-1 (Heckmann et al, 1998)), prostaglandins and leukotrienes (Eisen et al, 1977;Iwamoto and McBride, 1992), proteases (Hong et al, 1994;Patel et al, 1998;Fittkau et al, 2001), and prooxidant species. If the damage is not too severe, this is normally counterbalanced in time by production of anti-inflammatory cytokines, antiproteases, antioxidants, and heat-shock proteins leading to resolution of the inflammation (Barcellos-Hoff, 1993;Sierra-Rivera et al, 1993;Broski and Halloran, 1994;Sadekova et al, 1997;Roedel et al, 2002).…”
Section: Cellular Consequences Of Modulation Of Proteasome Activity Bmentioning
confidence: 99%
“…McKinney et al (10) reported that γ-irradiation (0.5-10 Gy) alone did not induce nitric oxide (no) production in J774.1 and RAW264.7 murine macrophages. However, human alveolar macrophages have been shown to release il-1 within hours of irradiation in vitro (11), and low-dose irradiation to induce IL-1 and IL-6 expression in mouse macrophages in vitro (12). araya et al (4) found that ionizing radiation enhanced the expression of MMP-2 in human lung epithelial cells in vitro, suggesting that MMP-2 is involved in radiation-induced lung injury.…”
Section: Introductionmentioning
confidence: 99%